Palinopsia associated with the CDK4/6 inhibitor ribociclib during the first-line treatment of metastatic breast cancer: two case reports - Martos, Tamara; Saint-Gerons, Marta; Masfarre, Laura; Castro-Henriques, Maria; Martinez-Garcia, Maria; Servitja, Sonia; Albanell, Joan (Frontiers in Oncology, 2024)
The most frequently used standard treatment for hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer patients consists of a CDK4/6 inhibitor (abemaciclib, ribociclib, or palbociclib) combined with endocrine therapy. Despite CDK4/6 inhibitors being part of routine care in the last few years, new adverse events continue to be reported. Here, we report two cases of palinopsia, a rare neurological visual disturbance that refers to the persistence or recurrence of a visual image after the removal of visual stimuli in patients treated with ribociclib and letrozole. Neuro-ophthalmological assessments and brain MRIs did not find any organic cause. However, palinopsia was related in a time- and dose-dependent manner to the intake of ribociclib. Following a one-level dose reduction of ribociclib, palinopsia was mild and well tolerated. Both patients continued the treatment with ribociclib, with one of them for almost 2 years. Based on the identification of two cases in our hospital in a short period of time, it is tempting to suggest that ribociclib-related palinopsias may not be uncommon. We propose that physicians should be aware of this ribociclib-associated adverse event. Patients presenting this symptom should undergo a routine workup (neuro-ophthalmological assessment and brain MRI) and, if negative, be reassured of its relation with ribociclib as well as the safety of continuing on this drug.